In silico analysis of RNA interference components and miRNAs-like RNAs in the seed-borne necrotrophic fungus Alternariabrassicicola. Issue 3 (March 2022) - Kwasiborski, Anthony; Bastide, Franck; Hamon, Bruno; Poupard, Pascal; Simoneau, Philippe; Guillemette, Thomas
Abstract: RNA interference is a mechanism of suppressing gene expression in plants, animals and fungi. This regulation mechanism involves three main enzymes, Dicers (Dcr), Argonautes (Ago) and RNA Dependent RNA Polymerases (Rdrp) allowing to produce smallRNAs. RNA interference and smallRNAs have a role in the plant–microorganisms interaction, either in a pathogenic or in a symbiotic relationships. Alternaria brassicicola is a pathogenic fungus of the Brassicaceae plants. During plant infection, it is able to transmit itself vertically and horizontally, giving advantages for new infection and dissemination. To investigate RNA interference and the presence of smallRNAs in A. brassicicola, an in silico analysis was achieved. Two DCR, 4 AGO and 3 RDRP genes were identified comforting the presence of smallRNAs in A. brassicicola . SmallRNA sequencing from wild-type strain and DCR deleted mutants allowed the identifcation of 17 miRNAs in A. brassicicola . The synthesis of these miRNAs is only weakly influenced by the inactivation of DCR genes suggesting the possible existence of an alternative Dicer-independent miRNA synthesis pathway. Target's prediction of A. brassicicola miRNAs identified genes in the fungus and in the plant model Arabidopsis thaliana . Some miRNAs were predicted to target A. thaliana genes involved in the methylation of histone and in the disease resistance.